Estimates of a-Value and b-value parameters for analysis of seismicity and potential hazard studies of earthquake disasters in the North Sumatra Region - Darmawan, Rangga Prasetyo; Halawa, Erniwati (EINSTEIN (e-Journal), 2026)
Tectonic activity in Indonesia, particularly in North Sumatra, is influenced by the interaction of the Indo-Australian and Eurasian plates, causing subduction and significant seismic activity. This study uses earthquake data from the International Seismological Centre (ISC) and the Gutenberg-Richter method to analyze seismicity, yielding an a-value of 9.9 and a b-value of 1.3. The results indicate a high level of seismic activity and a tendency for large earthquakes. The Magnitude of Completeness (Mc) of 5.1 ensures reliable earthquake data for magnitudes above 5.1. The 2000-2022 seismicity map indicates a concentration of shallow earthquakes in the southwest, related to active faults and the megathrust zone, with a more even distribution of moderate and deep earthquakes.